Neurophysiological evidence for underspecified lexical representations: asymmetries with word initial variations - Friedrich, C; Lahiri, A; Eulitz, C (American Psychological Association, 2008)
How does the mental lexicon cope with phonetic variants in recognition of spoken words? Using a lexical decision task with and without fragment priming, the authors compared the processing of German words and pseudowords that differed only in the place of articulation of the initial consonant (place). Across both experiments, event-related brain potentials indicated that pseudowords with initial noncoronal place (e.g., *Brachen) activate words with initial coronal place (e.g., Drachen [dragon]). In contrast, coronal pseudowords (e.g., *Drenze) do not as effectively activate noncoronal words (e.g., Grenze [border]). Thus, certain word onset variations do not hamper the speech recognition system. The authors interpret this asymmetry as a consequence of underspecified coronal place of articulation in the mental lexicon.